Genetic Counselors' Approach To Postmortem Genetic Testing After Sudden Death: An Exploratory Study. Issue 3 (September 2018) - Liu, Gina; MacLeod, Heather; Webster, Gregory; McNally, Elizabeth M.; O'Neill, Suzanne M.; Dellefave-Castillo, Lisa
A significant portion of sudden death cases result from an underlying genetic etiology, which may be determined through postmortem genetic testing. The National Association of Medical Examiners (NAME) recommends that an appropriate postmortem sample is saved on all sudden death cases under the age of 40. Genetic counselors (GCs) play an important role in this process by working with medical examiners and coroners (ME/Cs) to recommend and interpret specific testing and to guide family members. A survey sent to the National Society of Genetic Counselors was designed and implemented to learn more about the experiences of genetic counselors who had considered or ordered postmortem genetic testing. Results showed that cardiovascular GCs were significantly more willing to recommend genetic testing in younger age decedents (ages 10, 18, 30, 40, and 50) compared to other specialty GCs ( p <0.05, Chi-square). Thirty-seven percent (7 of 19) of GCs reported insurance covering some portion of genetic testing. Participants also reported highest success for DNA extractions with fresh and frozen blood, reinforcing NAME recommendations for appropriate sample collection for postmortem genetic testing. Overall, participating GCs demonstrated a very good understanding for the appropriate use of postmortem genetic testing and did identify suspected barriers of cost and lack of insurance coverage as deterrents. With the rapid decrease in costs for diagnostic genetic testing, ME/C awareness of NAME recommendations for sample collection and storage remain important to facilitate postmortem genetic testing.